Persepsi Guru Geografi dalam Penerapan Full day school di Kota Makassar - Satiljannah, K. Warat (LaGeografia, 2017)
The research used descriptive analysis technique to describe the results of research in accordance with the data obtained in the field about the perception of geography teachers in the application of full day school in Makassar. The results of this study indicate that 1) the perception of geography teachers in the application of full day school in Makassar is quite agree with the percentage of 38.24%, 2) obstacles experienced by the geography teacher during the implementation of full day school geography teacher is quite difficult in teaching during school hours and afternoon, the geography teacher is quite exhausted with the teaching schedule until the afternoon, and facilities that support full day school implementation is not adequate, 3) the solution in overcoming the constraints experienced by the geography teacher is the geography teacher must use approaches, methods and media more interesting learning , the geography teacher must be good at managing the time between teaching and resting as well as maintaining the body condition to keep the body fit, and the government must provide adequate facilities in supporting the implementation of full day school.